Ion source for Bendix Mass Spectrometer - Bendix Corporation (1970)
Close-up view of the ion source for a Bendix Corporation Time-of-Flight Mass Spectrometer. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources